Where is the apple pie - Gorbachev, Valeri. (Philomel Books, 1999)
A simple question leads to the description of a more and more outlandish situation, but never really gives an answer.
A simple question leads to the description of a more and more outlandish situation, but never really gives an answer.
Keywords: Questions and answers / Fiction.; Animals / Fiction.